Using the Implementation Centric Evolving Climate Change Adaptation Process to bridge the gap between policy and action - Wells, Cathie A.; Saggioro, Elena; Petty, Celia; Cornforth, Rosalind (Frontiers in Climate, 2023)
With climate impacts increasing in both frequency and intensity and unprecedented climate events having devastating results, the need for timely policy and action to support adaption is not in doubt. However, the gap between policy and action leaves many communities exposed to extreme events and vulnerable to loss of life and livelihoods. This is partly due to the difficulty policymakers face when confronted by climate projections with their inherent uncertainties. Competing sectoral interests and a lack of resources often compound such challenges. To address these issues, the Implementation Centric Evolving Climate Change Adaptation Process (ICECCAP) encases the climate risk assessment in an enabling framework to track resource, knowledge and regulatory needs. This process was applied as part of a UNEP project to support the National Adaptation Plan in Pakistan. A range of climate storylines, describing plausible climate futures and their potential environmental and socio-economic impacts, were developed and discussed with local stakeholders, including policy makers from across levels of governance. The process allowed us to translate complex physical science into narratives that could be communicated clearly to nontechnical national stakeholders, forming a basis for subsequent negotiation and decision-making at a local level to address multiple risks and respond to adaptation needs at this finer resolution. This reflects our aim, as part of the My Climate Risk network, to amalgamate bottom-up climate risk assessment with climate projection data that remains meaningful at a local scale. We show how the integration of scientific research and local expert stakeholder views can promote buy-in to adaptation planning. Grounded in a systemic and comprehensive understanding of potential impacts of climate change, this process has implications across socio-economic, environmental and governance spheres.